2010
DOI: 10.1007/s11618-010-0121-z
|View full text |Cite
|
Sign up to set email alerts
|

Dropouts am Gymnasium

Abstract: Zusammenfassung: Obwohl die Dropoutforschung auch hierzulande an Bedeutung gewinnt, konzentriert sie sich fast ausschließlich auf die gruppe der schulleistungsschwachen risikoschü-ler. Über Schulabgänge am gymnasium weiß sie jedoch fast nichts. Dieser Beitrag präsentiert die ergebnisse einer explorativen Studie zu Schulabbrechern am gymnasium. 102 vorzeitigen Abgängern und Abgängerinnen ("Dropouts") und 105 am gymnasium Verbleibenden ("Stabile") wurde ein Fragebogen vorgelegt, um informationen zu den gründen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In general, there is little research on dropout from academic tracks and the role of academic performance therein. Stamm (2010) found that Gymnasium dropouts in fact had worse grades on average, but most of them did not drop out because of their grades. Possibly, poor primary school grades are associated with other (unobserved) dropout-related factors like motivational problems, lower educational aspirations, social exclusion, or a general distance towards school.…”
Section: Discussionmentioning
confidence: 97%
“…In general, there is little research on dropout from academic tracks and the role of academic performance therein. Stamm (2010) found that Gymnasium dropouts in fact had worse grades on average, but most of them did not drop out because of their grades. Possibly, poor primary school grades are associated with other (unobserved) dropout-related factors like motivational problems, lower educational aspirations, social exclusion, or a general distance towards school.…”
Section: Discussionmentioning
confidence: 97%
“…However, this student population has the highest heterogeneity in terms of SES in Germany (Trautwein & Neumann, 2008). Academic track students from relatively low SES families have worse educational outcomes compared with academic track students from relatively high SES families: They perform worse in achievement tests (Ehmke, Hohensee, Heidemeier, & Prenzel, 2004), are at higher risk of dropping out of the academic track (Hillmert & Jacob, 2010; Stamm, 2010), and have a lower probability of attending a university after graduating from high school (Autorengruppe Bildungsberichterstattung, 2012; Hillmert & Jacob, 2005, 2010; Kramer et al, 2011). Thus, students’ SES still plays an important role in academic track schools in Germany, particularly concerning students’ achievement, transitions, and dropout.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, children with low academic preparedness may have a lower academic selfconcept, may have a harder time connecting with the teacher and classmates, or may only make friends with other low achievers. In turn, these factors may increase the risk of downgrading (Rumberger & Rotermund, 2012;Stamm, 2010).…”
Section: Ad-hoc Analysis Of Alternative Negative Experiencesmentioning
confidence: 99%